Quando três tempos se encontram: sentidos e ressignificações de jovens vivendo com HIV/Aids - Anjos, Degmar Francisco dos (2012)
The last Epidemiological Reports of AIDS, published by the Ministry of Health, revealed that, there is an increasing trend of this disease among youths. Correspondingly, studies indicate the existence of a social syndrome, or social epidemic, carried by prejudice and discrimination surrounding the disease. This fact generates negative psycho-emotional effects on people living who have been living with HIV/AIDS, especially the youths. Thus, this study is justified by the need of listening to the voice of the young people who have been living with HIV/AIDS, discussing the meanings related to the experiences with HIV/AIDS and associated issues, such as vulnerabilities, fears, managing and future perspective. The theoretical and methodological approach are guided by the Social Constructionism, which aims at comprehending the actions, social practices and systems of meanings in which people make sense of the world. This study objectified to investigate the meanings produced by young people who have been living with HIV/AIDS, on the experiences with HIV/AIDS, vulnerability to HIV/AIDS in youths, prejudice with people living with HIV/AIDS and the impact of positive diagnosis in their perspective the future. It was used a non-probability sampling, in which was selected a group of ten young participants who have been living with HIV/AIDS. The research was carried out through semi structured interviews consisting of four components: data identification, contextualization of way of living, issues related to vulnerability to HIV/AIDS and prejudice felt and issues related to living, interact with others and perspective of the future. The analysis occurred in three distinct stages: 1. Initial reading of transcripts, 2. Mapping the contents of the interviews and 3. Analysis of meanings revealed on the maps, starting three times: long, lived and short. As a result, it was observed 1- in a long time, emerged meanings related to the idea that there are still groups at risk, that HIV/AIDS was forgotten after the initial decreased of mortality and the fact of obtaining the positive diagnosis of HIV/AIDS is painful for remembering the deaths associated to AIDS in the past 2 in a lived time emerged meanings related to the realization that the programmatic and social vulnerabilities influenced in the individual vulnerability, due to the lack of empowerment on young people, the feminization HIV/AIDS is a consequence of the meanings associated to romantic love and gender inequality in the marital relationship and that socially constructed prejudice in the early years of the epidemic still materialize in the form of discrimination and stigmatization, and 3 in a short time the meanings associated to the perception that the fear of prejudice impacts on the everyday actions of young people, that it is necessary to structure managing strategies, often through the omission of diagnosis and even living with HIV/AIDS the participants comprehend the future as a construction process in which it is possible to have hope. In this context, it is concluded that strategies to limit the impact of the epidemic should have, at the same time, social and structural actions, which will depend on the actions of governments, organized social movements of Health and Human Rights, in addition to the development of the prevention programs, providing effective actions to combat socially constructed prejudices about the theme HIV / AIDS.